2007
DOI: 10.1002/xrs.993
|View full text |Cite
|
Sign up to set email alerts
|

Application of synchrotron‐radiation‐induced TXRF‐XANES for arsenic speciation in cucumber (Cucumis sativus L.) xylem sap

Abstract: Synchrotron-radiation-induced total reflection x-ray fluorescence (SR-TXRF) analysis was used for x-ray absorption near edge structure (XANES) measurements for the speciation of arsenic in cucumber (Cucumis sativus L.) xylem sap. The objective of the presented work was to exploit the advantages of the TXRF geometry for XANES analysis. Measurements were accomplished at the bending magnet beamline L of HASYLAB, Hamburg, Germany, using a Si(111) double crystal monochromator and a silicon drift detector (SDD). Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
1
30
0
2
Order By: Relevance
“…In past decades, a few experimental studies were performed utilizing the combination of TXRF and XANES, showing the applicability of the method to several analytical problems (e.g., [25,26,30,31]). As mentioned in the introduction, the motivation to utilize this powerful method is to extend XAS, and therefore chemical speciation, to samples that are available in small amounts (e.g., ll of solutions, ng of nanoparticles or aerosols, and thin films) and show elemental concentrations at the ppb level.…”
Section: Sr-txrf-xafs Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In past decades, a few experimental studies were performed utilizing the combination of TXRF and XANES, showing the applicability of the method to several analytical problems (e.g., [25,26,30,31]). As mentioned in the introduction, the motivation to utilize this powerful method is to extend XAS, and therefore chemical speciation, to samples that are available in small amounts (e.g., ll of solutions, ng of nanoparticles or aerosols, and thin films) and show elemental concentrations at the ppb level.…”
Section: Sr-txrf-xafs Analysismentioning
confidence: 99%
“…Furthermore, if the SR is monochromatized with a high-resolution crystal monochromator, instead of a wide band pass system such as a multilayer, the technique can be extended to X-ray absorption spectroscopy (XAS) to gain chemical information on a specific element of interest [25][26][27][28][29]. Monochromatization results in a flux reduction of about two orders of magnitude, but it is still sufficient for X-ray absorption near edge structure (XANES) analysis at ppb level [25,26,30,31]. This allows an extension of XAS to: (1) the trace-element level in droplet samples where only small amounts are available [25,26]; and, (2) the investigation of thin-layered materials and implantations utilizing the GI-XRF set-up.…”
Section: Introductionmentioning
confidence: 99%
“…The self-absorption effect results in a damping of the oscillations ͑reduced maxima and enhanced minima͒ of the absorption fine structure and was previously observed when measuring samples with higher elemental concentrations in TXRF geometry. [18][19][20] It was shown by calculations and measurements that this effect occurs due to the absorption of the incident beam along its path through the sample ͑which is especially long for TXRF geometry͒. 19 The path length is equivalent to the penetration depth of the incident beam and is therefore energy dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Rosas‐Castor et al reviewed in publication their investigations on the phytotoxicity processes and the uptake mechanism in maize crops: The As(V) is transported via the xylem to the other parts of the plant and stored mostly in the cell vacuoles. The xylem sap was analysed by XANES, and the result of these experiments demonstrated that As(V) absorbed by cucumber roots from Hoagland's solution was reduced to As(III). In other experiments, similar results were reported that roots took up the As(V), and it was partly reduced to As(III) inside mesquite plant and pea .…”
Section: Introductionmentioning
confidence: 99%